Mass transfer aspects of 3D cell cultures in tissue engineering. Issue 3 (28th March 2014) - Mekala, Naveen Kumar; Baadhe, Rama Raju; Potumarthi, Ravichandra
ABSTRACT Tissue engineering strategies involving in vitro growth of cells over three‐dimensional scaffolds before implantation into the damaged portions represents a significant alternative to current clinical treatment methods. In order to improve this in vitro cell culture system, we need to focus on various engineering aspects, and each aspect has its own advantages and limitations. Undoubtedly, these engineering factors are critical for the successful development of tissues and organ products and the tissue engineering industry as well. These issues include elements of mass transport, biomaterials, biomechanics, and so on. Our focus in this review paper is to discuss the alternative strategies to overcome the mass transfer limitations in the three‐dimensional constructs, which have been widely researched for the tissue engineering purposes. © 2014 Curtin University of Technology and John Wiley & Sons, Ltd.